166 Changes in e-c coupling proteins and transverse and axial tubular structures in guinea pig ventricular muscle during pre- and post-natal development to adulthood. (5th June 2017) - Kashbour, Hanan; Taggart, Michael; White, Kathryne
Abstract : Transverse tubules (TT), plasmalemma invaginations perpendicular to the long axis of the cardiomyocyte, facilitate rapid action potential transmission to the cell interior and efficient cardiac excitation-contraction coupling (ECC). Tubule alteration and changes in expression of proteins important for normal ECC have been noted in heart disease. The aim of this study is to explore the changes of selected ECC-related protein expressions, and transverse tubular structures, from pre- and post-natal cardiac development to adulthood in guinea pig ventricular muscle. Hearts were collected from guinea pigs at developmental stages: fetal (between gestation days (G) 55–68; term=G67–68); neonatal week one (NW1), two (NW2) and three (NW3); and adult. Hearts were flushed with a cold cardiologic solution and (i) left ventricles (LV) frozen for subsequent protein analysis by western blotting or (ii) retrogradely perfused with fixative and LV processed for ultrastructural examination by serial block face-scanning electron microscopy. Values are mean± SEM, compared by one-way ANOVA and Bonferroni posthoc test (p<0.05). Expression of Î² adrenoceptor, TT marker, increased in adults (0.87±0.14 fold relative to positive control) and neonates NW2 (0.90±0.04 fold) compared to fetal G55/57 (0.44±0.04 fold) or neonates NW1 (0.5±0.04 fold). Junctophilin2, a determinant of TT integrity, was expressed in G55/57 and, surprisingly, was invariant among the biological groupings. Analysis of digitally reconstructed (Amira 6.0) serial EM images revealed developmental changes in cardiomyocyte structure. Sarcomere length narrowed from G55/57 (2.28±0.01 µm) to NW1 (1.90±0.01µm) and adult (1.92±0.01 µm); assessing 250 sarcomeres. Total tubular volume increased from 0.68±0.08% at G64/68 to 2.54±0.48% in the adult. Fetal cardiac TTs appear as early as the mid-third trimester of guinea pig pregnancy. Changes in TT/TAT abundance through pre- and post-natal development to adulthood mirror the changes in expression of some (Î² adrenoceptor) but not other (junctophilin2) proteins likely to be important for maturation of ECC. TT formation may start prenatally but it is less organised.